Músicos, productores y audiencias, cercanía desde la mediación social y tecnológica en Colombia - Sandra Velásquez; Tatiana López; Fabián Valverde (Les Cahiers ALHIM)
Music is one of the cultural and creative industries that has changed the most owing to the technologies of information and communication (ICT). News about the death of this industry, the concentration of majors, copyright problems, download platforms, different audio devices, the increase of independent productions and the multinational organizations on internet, sonorities known outside their place of origin and the musicians’ new work forms without barriers of space and time, are subjects of analysis in the academia, in the media, on musicians’ encounters, and costumers’ conversations. This article, on its first part, presents a close-up to the reality of proximity among musicians, producers and audiences, resulting from the research work carried out in different pieces of work about the situation in Colombia. In the second part, it presents two cases related to the interaction using social and technological networks: the perception of El Festival de la Bandola and its impact on cultural development and also the support from cultural management in order to strengthen musicians linked with the platform Así Suena in four departments of Colombia.